DEVELOPMENT OF MUCOADHESIVE DELIVERY OF CHLORZOXAZONE POLYETHYLENE GLYCOL SOLID DISPERSION - Jagdale, Swati C; Hable, Asawaree A; Chabukswar, Aniruddha R; Kuchekar, Bhanudas S (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Chlorzoxazone (CLZ) is centrally acting skeletal muscle relaxant. It is insoluble in water, so employed for the formation of solid dispersions (SD) as a means to enhance the dissolution rate, and carrier selected was polyethylene glycol 6000 (PEG 6000). Methods: The SDs were prepared by different methods and characterized by in vitro drug release, drug content, fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry, powder X-ray diffraction. All the SD showed dissolution improvement compare to pure drug. These techniques revealed distinct loss of drug crystallinity in the formulation accounting for enhancement in dissolution rate. The SD methods showing best in vitro drug release profile were selected in the further development of mucoadhesive buccal patches. A buccal patch has been developed using two mucoadhesive polymers, i.e. hydroxyl propyl methyl cellulose K4M and carbopol 974. The patches were evaluated for the physicochemical, mechanical and drug release characteristics. The optimized patches showed good mechanical and physicochemical properties to withstand the environment of the oral cavity. The in-vitro permeation study showed that patches could deliver drug to the oral mucosa for a period of 8 hrs. Results: The results indicate that suitable bioadhesive buccal patches with good permeability could be prepared. The batches FH4 and FC4 showed 81.95% and 79.97% permeated through goat mucosa membrane in 8 hrs. The physicochemical interactions were investigated by FTIR, showed no any evidence of interactions and were present in an unchanged state. The stability study for SD and buccal patch carried out revealed that were stable for a period of 3-month. Conclusion: Phase-solubility studies indicate significantly increase in solubility. The optimized buccal patches showed good mechanical and physicochemical properties to withstand environment of the oral cavity. Keywords: Solid dispersions, Chlorzoxazone, Dissolution studies, Buccal patch, In vitro permeation studies.